Utilization Of Shrimp Shell Waste As A Flavor Enhancer: An Outreach Program At Penang Malaysia - Hasanah, Sabila; Gunawan, Fikri Iqlilah; Maharani, Tiara; Ramadhan, Ihza Zhafran; Widiana, Ana (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Penang, one of the 13 states in Malaysia, is renowned for its shrimp farming, which generates a substantial amount of waste, primarily in the form of shells, heads, and other inedible parts. High shrimp production, such as the 10,477.62 metric tons produced in 2015, significantly contributes to the local economy but also poses environmental challenges like water pollution, foul odors, and disease risks if the waste is not properly managed. This protein and glutamate-rich shrimp waste can be processed into natural flavor enhancer powder to replace MSG, reducing waste while providing economic and educational benefits to the community. The processing involves cleaning, boiling with salt and sugar, grinding, straining, and drying until it becomes a fine powder. From 2 kg of raw materials, about 500 grams of dried or powdered shrimp flavor enhancer can be produced, depending on the level of drying and final processing. This program aims to reduce pollution, increase community income, and serve as an educational reference.